Kolaborasi Content Marketing dan Event Marketing sebagai Strategi Meningkatkan Loyalitas Pelanggan Wisata Korea Fantasy - Skadinavion, Mochamad Oktian Desta; Aliami, Sri (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2024)
Research aim: Determine the collaboration of content marketing and event marketing as a strategy to increase customer loyalty of Korea Fantasy Kediri Tourism. The research approach uses qualitative with case studies. Approach: Data collection techniques include interviews, observations, and online and offline documentation. Data validation uses data source triangulation. Research Finding: The results of the study: (1) Content marketing through content creation begins with conceptualizing and sharing ideas, photos and videos uploaded at any time and does not yet have a special team. Content sharing uses social media and TikTok as superior media, connecting through the government, hotels, restaurants, universities/schools, and communities and for community buildings using social media and meetings. (2) Event marketing through the enterprise by creating events that are in accordance with the event and attractive, entertainment by inviting popular artists and creating events that have value benefits, excitement through events that create happiness, pride, and satisfaction. Originality: This research shows content and event marketing collaboration can create a more immersive customer experience. Companies can significantly increase customer engagement by combining engaging content and interactive events. Practitioner implication: Social media is important for promoting events and content. Companies can use these platforms to invite participation, spread information, and build momentum. Research limitation: The rapidly changing marketing environment may affect the relevance of the strategies proposed in this study. Trends or consumer preferences could make the strategy less effective over time.